Hydrogeomorphological changes and the erosion-deposition impact in the San Francisco River Basin, northwest Argentina: a multidecadal analysis (Latin American Journal of Sedimentology and Basin Analysis, 2024)
Modifications of wetland and forest areas are studied, in particular, to establish to what extent they are sensitive to natural changes (e.g., increased precipitation and/or temperature) in addition to human activities (e.g., advancing agricultural frontier, deforestation, channelizations). The San Francisco River Basin (SFRB; 1,789 km2) is located in the Northwest of Argentina in the Geological Province of Nortwestern Pampean Ranges (Sierras Pampeanas Noroccidentales), between 27°40'S and 28°25'S, and 65°15'W and 65°45'W). In recent decades, agricultural development and management in the middle and lower SFRB generated rural channelizations (the largest of 10 km at the basin outlet between 2005-2015), drainage of wetland forests, deforestation of native dry forest since 1995 and changes in land use. In addition, a 200 mm increase in mean annual rainfall since 1972 and an increase in extreme hydrological events, are registered. These modifications produced changes in local base level, erosive processes of retreat and the development of new river channels from upstream, increasing flow velocities, flow rates, and sediment discharge. The intensified erosive processes resulted in four new river courses in the middle and lower basin, incorporating the SFRB into the Marapa river basin, changing from arheic to endorheic behaviour, and generating the contribution of liquid and solid flows to the system of which it is now a part. The aim of this study is to examine the development of the new hydrographic network within the SFRB between 1990 and 2018 and to calculate the solid and liquid discharges generated by the new network. The hydrographic network formed by the rivers El Abra, Ovanta, San Francisco and Suncho creek, was digitized in the open-source software QGIS 3.18.3 on the basis of the visual interpretation of satellite imagery. The lengths of the rivers were automatically calculated and exported to a spreadsheet to determine the downstream expansion of the river network. Measurements and sampling of water discharge and sediment load were performed monthly in the lower section of the SFRB. The float and cross-section method was used to quantify the flow rates, and the sediment samples were filtered, dried in an oven for 24 h and weighed on a precision balance to obtain the sediment concentration (C in mg/l). The study determined the generation of 102 km of new river channels in a 28 yr period. The hydrographic network had an annual sediment production of 82,138 t/yr and an annual discharge of 21,96 hm3, contributing to the Marapa river basin and generating an acceleration in the silting of the downstream Río Hondo reservoir. This work provides a basis for management and mitigation of erosion and flooding problems in the area.
Keywords: river basin; flow; solids transport; anthropic activity; northwest Argentina